Layanan Calistung Terhadap Anak Pemulung (Calistung Learning Service For The Children Who Work As A Scavenger) - Fahruroji, Komarudin Afz (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2012)
The children who are in their primary education and who have to leave their pupilage can still be found in some parts of the city and village. They are God-given mandate for their parents. However, there is lack of fortune that causes them leaving their pupilage. They actually want to learn just like other children in their age, but because of a reason they cannot continue their education. They are the children who work as a scavenger. They look for rubbish generated by households and markets. Teaching about CALISTUNG (reading, writing, and arithmetic)to them needs patience and a serious attention because they are not easy to be assemble in the same time and place. Therefore, the method of learning CALISTUNG that can be applied is incidental method (learning by doing) which can be applied when we meet them in their hangout. Learning CALISTUNG can be implemented in this way even if the result is not perfect as expected. The result of study can be obtained by pre-test, the process of learning, and post-test. The test cannot be done by all of the participants. The total of participants is 14 people, but there are only 9 participants who can attend the learning process and show the progress in learning CALISTUNG.